A CMOS chip for individual cell manipulation and detection. - Manaresi, N. (IEEE Journal of solid state circuits)
Manipulation of populations of living cells on an individual basis is essential for the investigation of complex interactions among cells. We present a new approach to the integration on silicon of dielectrophoretic actuators and optical sensors that allow us to carry out this task. The device presented in this paper is an 8×8 mm2 chip implemented in a two-poly three-metal 0.35-μm CMOS technology, featuring 102,400 actuation electrodes, arranged in an array of 320×320, 20 μm×20μm microsites each comprising addressing logic, an embedded memory for electrode programming, and an optical sensor. The chip enables software-controlled displacement of more than 10,000 individual living cells, allowing biologists to devise complex interaction protocols that are impossible to manage otherwise. The manipulation does not damage the viability of the cells, so that this approach could be a unique extension to the techniques already available to biologists.